(untitled) (Journal of Nepal Geological Society, 2009)
In central Nepal, medium- to high-grade rocks of the Kathmandu Complex overlie lower-grade metamorphic rocks of the Nawakot Complex. These two units are separated by a clear high strain thrust belt marked by mature dynamic recrystallisation. These rock sequences have been folded to form the NW-SE trending, essentially upright Mahabharat Synclinorium. Whole rock Sm-Nd isotopic analysis was carried out in thirteen samples collected from the Nawakot Comp lex, Kathmandu Complex, and the thrust zone between these two rock sequences from different parts of central Nepal. This analysis demonstrates important distinctions between the two rock packages. Results show a clear linear array of the data points from the different units in a 143Nd/144Nd vs. 147Sm/144Nd isochron plot with lowest values in the Nawakot Complex phyllite and highest values in the Kathmandu Complex gneiss while Ꜫ(0) Nd values show a marked difference with Nawakot Complex rocks ranging at -20 or higher, while the Kathmandu Complex rocks range at about -13 in schist and at about-6 in gneiss giving rise to major differences in their model ages. The comparison of the obtained data from the previous one clearly shows the affinity of the Nawakot Complex rocks with the Lesser Himalayan Sequence and of the Kathmandu Complex with the Higher Himalayan Sequence.